THE EFFECT OF ELECTRON-RICH HETEROATOMS IN METALLABORANE CLUSTERS - LUPAN, Alexandru; ATTIA, Amr A.A.; KING, R. Bruce (Studia Universitatis Babeș-Bolyai Chemia, 2016)
The experimentally synthesized and structurally characterized metallaborane clusters containing highly electronegative heteroatoms namely (S, P, and Se) were studies by density functional theory in order to provide an insight into the influence of these heteroatoms on the polyhedral framework of metallaboranes.